The digital economy in Algeria - Derbal soumeia; Ben Lamoudi djalila; Boussouek amel (University of Eloued, 2024)
Over the past two decades, the digital economy has emerged as a key driver of growth, productivity, and competitiveness for businesses and nations alike. Algeria, like many countries worldwide, has embraced digital transformation as a strategy to diversify and strengthen its economy. The foundations for a digital economy in Algeria were laid in the 2000s, notably with the enactment of Law No. 2000-03 on August 5, 2000, which established general regulations for postal and telecommunications services. This law aimed primarily at fostering competition within the telecommunications sector. This research adopts an analytical-descriptive approach to explore the subject matter. Concepts are first presented descriptively and subsequently analyzed to achieve the study's primary objective: evaluating the integration of digitization into Algeria's economic activities. By examining the theoretical and practical dimensions of this integration, the study aims to highlight Algeria’s efforts to align with emerging and developed countries in leveraging technological advancements in information and communications
prospects and challenges
Intervention
Keywords: Digitization; E-commerce; E-marketing; Digital Technologies